An exploratory analysis of the dynamics of the activity of the Fiscal Anti-fraud Directorate General in the 2014-2020 period at the level of Romania - Aivaz, Kamer-Ainur; Munteanu, Ionela Florea; Chiriac, Alina (Technium Social Sciences Journal, 2022)
The Fiscal Anti-fraud Directorate General (DGAF) is a structure of the Romanian public authority whose primary objective is the fight against tax evasion and tax and customs fraud. The activity of investigating fraud and dismantling the transactional chains that lead to prejudicing the state budget is important both from a financial point of view and from a social point of view and it contributes to building trust in the safety and integrity of the tax system. Given the need for a sustainable legal framework for fighting against evasion and taking into account the importance of a unitary control mechanism able to eliminate parallelisms or divergences in the assessment of economic operations, the research focuses on the analysis of the dynamics of the activity of the Fiscal Anti-fraud Directorate General by means of the indicators reported by the institution. The paper allows the identification of certain correlations or interdependencies between the specific indicators of the fraud investigation activity, as well as the foreshadowing of some areas for normative improvement related to the reporting of the results of the anti-fraud activity. The reduction of tax evasion and the increase in collected budget revenues are objectives that convey a strategic importance to DGAF’s activity, so that the research of the indicators reported by this structure of public authority produces an image of the degree of economic compliance and the compliance with the premises of fiscal fairness and equity.